Migration and health: a global public health research priority - Kolitha Wickramage; Jo Vearey; Anthony B. Zwi; Courtland Robinson; Michael Knipper (BMC, 2018)
Abstract Background With 244 million international migrants, and significantly more people moving within their country of birth, there is an urgent need to engage with migration at all levels in order to support progress towards global health and development targets. In response to this, the 2nd Global Consultation on Migration and Health- held in Colombo, Sri Lanka in February 2017 - facilitated discussions concerning the role of research in supporting evidence-informed health responses that engage with migration. Conclusions Drawing on discussions with policy makers, research scholars, civil society, and United Nations agencies held in Colombo, we emphasize the urgent need for quality research on international and domestic (in-country) migration and health to support efforts to achieve the Sustainable Development Goals (SDGs). The SDGs aim to 'leave no-one behind' irrespective of their legal status. An ethically sound human rights approach to research that involves engagement across multiple disciplines is required. Researchers need to be sensitive when designing and disseminating research findings as data on migration and health may be misused, both at an individual and population level. We emphasize the importance of creating an 'enabling environment' for migration and health research at national, regional and global levels, and call for the development of meaningful linkages - such as through research reference groups - to support evidence-informed inter-sectoral policy and priority setting processes.